PENGARUH DESAIN INTERIOR TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Restoran Lavenrice Bengkulu) - Ramadhan, Alman Fajar; Ratnawili, Ratnawili (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The title of this research is The Influence of Interior Design on Consumer Purchasing Decisions (Case Study on Lavenrice Bengkulu Restaurant Consumers)” just in time. This research influences the importance of purchasing decisions, several factors that influence purchasing decisions are Interior Design. This study aims to analyze the influence of interior design on consumer purchasing decisions at the Lavenrice Bengkulu Restaurant."Th e research method used is a quantitative method with an associative quantitative approach. The population in this study were consumers of the Lavenrice Bengkulu Restaurant. The number of respondents in this study were 110 people. Methods of data collection using observation and questionnaires.Based on the results of simple linear regression, the regression equation form Y = 11.108 + 0.377 (X1) The results of the research and hypothesis testing show that Interior Design is t hit>t table (6.216 > 1.659) and (sig α = 0.000 <0.050), this states that there is a significant influence of Interior Design on purchasing decisions at Lavenrice Bengkulu. Keywords: Interior Design, Purchase Decision